Wheelchair Basketball World Championships 2018 - Player survey on training environment and health complaints - Kluge, S.; Zech, A.; Richarz, P.; Riepenhof, H.; Junge, A.; Hollander, K. (Deutsche Zeitschrift für Sportmedizin, 2021)
Problem: Little is known about health complaints and their prevention in elite wheelchair basketball. The study aimed to survey training environment and health complaints of elite wheelchair basketball players in the 12 months prior to the Wheelchair Basketball World Championships 2018 (WBWC).